Trophic transfer of chlorinated paraffins and their under-studied structural analogues in a freshwater lake food web - Xinyu Du; Yaqing Li; Ruihe Jin; Yan Wu; Tian Lin (Environment International)
Chlorinated paraffins (CPs) are high production volume chemicals that encompass diverse CP structural analogues (CPSAs). Nevertheless, little is currently known about the trophic transfer of long-chain CPs (LCCPs) and CPSAs. In this study, the occurrence, homologue patterns, and trophic dynamics of short-chain (SCCPs), medium-chain (MCCPs), and LCCPs (C10-20) were investigated in a typical freshwater lake food web in Shanghai, China. Total CP levels ranged from 490 to 20,000 ng/g lipid weight in biota, dominated by MCCPs. The trophic magnification factors (TMFs) of SCCPs, MCCPs, and LCCPs were 1.87, 1.78, and 1.59, respectively. All CP homologues including 19 LCCP homologues (C18-20) exhibited significant trophic magnification potential (TMF > 1). Moreover, six CPSA groups including chlorinated olefins, sulfite esters, aliphatic sulfates, nitrate esters, and fatty acid esters were for the first time positively identified and semi-quantitated in wildlife. The consistent linear correlations between CPSA and CP burdens in biota, along with the similar CPSA homologue patterns found in biota and CP technical mixtures for most CPSA groups (4 out of 6), suggest that these CPSAs primarily originate from the release and bioaccumulation of CPSAs in commercial CP products. Similar to CPs, most identified CPSAs exhibited both biomagnification and trophic magnification potential in the freshwater ecosystem. This study enhances understanding of bioaccumulation characteristics of all the CP groups and their less-known structural analogues.